2023
DOI: 10.1001/jamanetworkopen.2023.23064
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic Characteristics and Mental and Physical Health Diagnoses of Yazidi Refugees Who Survived the Daesh Genocide and Resettled in Canada

Nour Hassan,
Annalee Coakley,
Ibrahim Al Masri
et al.

Abstract: ImportanceThe health status of Yazidi refugees, a group of ethnoreligious minority individuals from northern Iraq who resettled in Canada between 2017 and 2018 after experiencing genocide, displacement, and enslavement by the Islamic State (Daesh), is unknown but important to guide health care and future resettlement planning for Yazidi refugees and other genocide victims. In addition, resettled Yazidi refugees requested documentation of the health impacts of the Daesh genocide.ObjectiveTo characterize sociode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Overall, 18% of total diagnoses coded among our cohort (285/1535 diagnoses) were physical symptoms recently identified as suspected somatoform disorders by refugee clinician consensus. 22 Table 4 shows the prevalence of ICD-10 diagnoses identified as clinician consensus-derived suspected somatoform disorders by age group. The most frequently coded diagnosis suspicious for a somatoform disorder by clinicians for both adults and children was abdominal and pelvic pain (26·3%, 60/228 adults; 6·32%, 11/174 pediatric patients), followed by low back pain for adults (20·2%, 46/228) and joint pain for children (4·0%, 7/174).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Overall, 18% of total diagnoses coded among our cohort (285/1535 diagnoses) were physical symptoms recently identified as suspected somatoform disorders by refugee clinician consensus. 22 Table 4 shows the prevalence of ICD-10 diagnoses identified as clinician consensus-derived suspected somatoform disorders by age group. The most frequently coded diagnosis suspicious for a somatoform disorder by clinicians for both adults and children was abdominal and pelvic pain (26·3%, 60/228 adults; 6·32%, 11/174 pediatric patients), followed by low back pain for adults (20·2%, 46/228) and joint pain for children (4·0%, 7/174).…”
Section: Resultsmentioning
confidence: 99%
“…20,21 When compared with a recent Yazidi refugee analysis using expert clinician consensus to identify potential trauma-related conditions, we found that one-fifth of diagnoses (18%) made among our cohort were on a consensus list of non-specific diagnoses clinicians suspected represented somatoform disorders. 22 This proportion suggest the importance of adopting a culturally sensitive approach to diagnosing mental health illnesses among Afghan and other refugees despite potential reluctance, at times, to openly discuss mental health. 33 Following the Taliban's takeover, our team has observed a significant linguistic and cultural shift among Afghan refugees settled locally.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations